Research on ecological quality and restoration of fragile mining areas in the Yellow River Basin—The case of Xiegou coal mine - Xin Sui; Yiming Sun; Xuan Wang; Jin Yuan (Ecological Indicators)
Coal mining can seriously damage the ecological quality of the environment, especially in the ecologically fragile areas of the Yellow River Basin. Thus, a detailed analysis of the spatiotemporal dynamics and drivers of ecological quality in fragile coal mining areas is vital for ensuring the ecological security of the Loess Plateau and restoring the Yellow River Basin’s ecosystems to support sustainable development. The Google Earth Engine (GEE) platform enables efficient extraction of long-term remotely sensed data, significantly enhancing monitoring capabilities for temporal analysis. Therefore, this study evaluates the ecological quality of the mining area for 20 years (2002–2022) based on the Remote Sensing of Ecology Index computed by GEE on a 30 m grid scale in an all-round way of spatial heterogeneity, spatial statistics and trend analysis and combines it with the ecological network constructed through landscape ecology to provide opinions on ecological restoration of the mining area. The results show that (1) the overall ecological quality of the study area shows a decreasing trend, and the change in ecological quality is closely related to urban development and coal mining. (2) The distribution of ecological quality is correlated, with high-value areas concentrated in the gently sloping vegetation areas in the south and north, and most urban and peri-urban areas are low-value areas. (3) Among the drivers of ecological quality, Net Primary Productivity mainly positively affects the central urban area and negatively affects the steep-slope areas in the north and south. Normalized Vegetation Index positively affects the central and southern areas and negatively affects the urban and higher elevation areas. Temperature positively affects the southeastern portion of the study area and negatively affects the rest of the area, especially the areas with higher slopes, which have significant negative impacts. Precipitation has negative impacts, mainly in urban areas. (4) In terms of the development trend of ecological quality, the proportion of land with ecological deterioration in the future is 53.72 %, which is mainly distributed in the urban, mining, and southeastern areas, and the proportion of areas with ecological improvement in the future is 44.42 %, which is distributed in the northern and southwestern areas with gentle slopes. The ecologically fragile areas of the Yellow River Basin are characterized by complex geological conditions and multifactorial influences, necessitating urgent restoration. This study proposes a hierarchical restoration framework by integrating spatiotemporal ecological quality analysis with an ecological network model (constructed through ’ecological source-resistance surface-corridor’ principles): ’one core, two subzones, three belts, and four nodes.’ This approach aims to enhance ecosystem resilience and guide targeted interventions. By quantifying and visualizing the ecological quality as well as influencing factors of the ecologically fragile small-scale mining area and combining the ecological network of landscape ecology, the ecological restoration of the study area is proposed, which is conducive to the optimization of the ecological space of the small-scale mining area, the enhancement of the biological environment, and the promotion of ecological restoration from the theoretical point of view.